PENGARUH STRUKTUR MODAL DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA - Diah Manda Sari; Emilia Gustini; Lukita Tripermata (Jurnal Ilmiah Ekonomi Global Masa Kini)
This study aims to determine the effect of capital structure and financial performance of the company's value. This study uses secondary data from the company's financial statements. Samples and sampling using purposive sampling techniques. Analysis of data using classic assumption test and multiple linear regression. Indicators of this research capital structure is debt to equity ratio (DER). Financial performance indicators, namely return on assets (ROA). Indicators of the company's value is the price book value (PBV). The study population was banking companies listed in Indonesia Stock Exchange period 2010-2014. The results of the study explains that there is significant influence simultaneously DER and ROA independent variables and the dependent variable PBV. No effect and partial significant independent variable DER on the dependent variable PBV. There is a significant effect partially independent variables ROA on the dependent variable PBV.Key word: Capital Structure, Financial Performance, Value Company